A Comparative Energetic Analysis of Active and Passive Emission Control Systems Adopting Standard Emission Test Cycles. (19th November 2012) - Algieri, Angelo; Amelio, Mario; Morrone, Pietropaolo
Abstract : The present work aims at analysing and comparing the thermal performances of active and passive aftertreatment systems. A one-dimensional transient model has been developed in order to evaluate the heat exchange between the solid and the exhaust gas and to estimate the energy effectiveness of the apparatus. Furthermore, the effect of the engine operating conditions on the performances of emission control systems has been investigated considering standard emission test cycles. The analysis has demonstrated that the active flow control presents the higher thermal inertia and it appears more suitable to maintain the converter initial temperature level for a longer time after variations in engine load. Conversely, the traditional passive flow control is preferable when rapid "cooling" or "heating" of the solid phase is requested. Moreover, the investigation has highlighted the significant influence of the cycle time and converter length on the energetic performances of the aftertreatment apparatus.